1982
DOI: 10.1111/j.1365-2621.1982.tb11048.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soluble and Bound Peroxidase—IAA Oxidase During Tomato Fruit Development

Abstract: Soluble peroxidase activity increased dramatically during the early stages .of tomato fruit development, reaching a maximum at the mature-green stage. Ionically and covalently bound peroxidases were also observed, and the activities of these fractions increased steadily throughout fruit development. IAA (indoleacetic acid) oxidasc activity was observed in both soluble and bound fractions and paralleled the peroxidase activity. Tissue homogenates from juvenile fruit caused an extended induction period in IAA ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(74 citation statements)
references
References 20 publications
0
74
0
Order By: Relevance
“…Portions (0.5 g) of lyophilized corn root samples were stirred in 10 ml of 1 M potassium acetate (pH 6.0) for 2 h at 4°C. The mixtures were centrifuged, the supernatants were dialyzed and lyophilized, and the residues were resuspended in 20 mm sodium phosphate (pH 6.0) and assayed for peroxidase activity by monitoring guaiacol oxidation (25). RESULTS …”
Section: Methodsmentioning
confidence: 99%
“…Portions (0.5 g) of lyophilized corn root samples were stirred in 10 ml of 1 M potassium acetate (pH 6.0) for 2 h at 4°C. The mixtures were centrifuged, the supernatants were dialyzed and lyophilized, and the residues were resuspended in 20 mm sodium phosphate (pH 6.0) and assayed for peroxidase activity by monitoring guaiacol oxidation (25). RESULTS …”
Section: Methodsmentioning
confidence: 99%
“…POD activity was measured as described by Thomas et al (1982). The reaction mixture contained 3 ml of phosphate buffer (pH 7.0), 1.0 ml of 0.18% H 2 O 2 , 1.0 ml of enzyme extract, and 1.0 ml of 0.1% guaiacol.…”
Section: Determination Of Antioxidative Enzyme Activitymentioning
confidence: 99%
“…The role of soluble POD in RS development is unclear. It seems that soluble POD is not involved in the process of cell wall lignification, since cytochemical studies have shown that soluble POD exists in the inner face of the tonoplast (17,18), whereas the oxidation of phenolic precursors for lignin formation occurs in the cell wall (4,11,12).…”
mentioning
confidence: 99%
“…This increase in ionically bound POD activity is consistent with the increase in lignin biosynthesis in RS cell walls, since free phenolic precursors must be oxidized by POD to form lignin polymers. Several researchers (3,17,18) have suggested that ionically bound POD exists in plant cell walls. Soluble POD activity was very high in both the air control and ethylene-treated tissues (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation